Peptoid‐Directed Formation of Five‐Fold Twinned Au Nanostars through Particle Attachment and Facet Stabilization. Issue 14 (15th March 2022) - Jin, Biao; Yan, Feng; Qi, Xin; Cai, Bin; Tao, Jinhui; Fu, Xiaofeng; Tan, Susheng; Zhang, Peijun; Pfaendtner, Jim; Naser, Nada Y.; Baneyx, François; Zhang, Xin; et al.
Abstract: While bio‐inspired synthesis offers great potential for controlling nucleation and growth of inorganic particles, precisely tuning biomolecule–particle interactions is a long‐standing challenge. Herein, we used variations in peptoid sequence to manipulate peptoid–Au interactions, leading to the synthesis of concave five‐fold twinned, five‐pointed Au nanostars via a process of repeated particle attachment and facet stabilization. Ex situ and liquid‐phase TEM observations show that a balance between particle attachment biased to occur near the star points, preferential growth along the [100] direction, and stabilization of (111) facets is critical to forming star‐shaped particles. Molecular simulations predict that interaction strengths between peptoids and distinct Au facets differ significantly and thus can alter attachment kinetics and surface energies to form the stars. This work provides new insights into how sequence‐defined ligands affect particle growth to regulate crystal morphology. Abstract : By taking advantage of the easy manipulation of peptoid–peptoid and peptoid–particle interactions solely by the variation of side chain chemistry, peptoid‐induced formation of five‐fold twinned Au star‐shaped particles exhibiting five regular points has been achieved through a process of repeated particle attachment followed by facet stabilization.